1994
DOI: 10.1152/jn.1994.72.6.2737
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization-activated Na(+)-K+ current (Ih) in neocortical neurons is blocked by external proteolysis and internal TEA

Abstract: 1. After 1 day in culture, neurons derived from the neonatal cerebral cortex of the rat exhibited a slowly activating current gated by hyperpolarizing voltage clamp pulses. The current was blocked by extracellular Cs+ and unaffected by extracellular Ba2+, and was permeable to both Na+ and K+ (PNa/PK = 0.29). Its form and pharmacology are consistent with a current termed Ih in other preparations. 2. Ih was absent from cells acutely dissociated from both the neonatal and mature cerebral cortex, despite the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…The acid-gated currents were not inhibited by a mixture of antagonists to ionic channels gated by glutamate (20 M 6-cyano-7-nitroquinoxaline-2,3-dione͞50 M 2-amino-5-phosphopentanoic acid), GABA (20 M bicuculline), and acetylcholine (1 M atropine͞5 M mecamylamine). In these experiments, voltage-gated sodium current was inhibited by extracellular tetrodotoxin (1 M), and voltage-gated current activated by hyperpolarization (I h current) was inhibited by intracellular QX-314 (5 mM) or tetraethylammonium (50 mM) (20,21). The dose-response relationship for activation by protons had an apparent Hill coefficient of 1.0 and an apparent EC 50 of pH 5.5 (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The acid-gated currents were not inhibited by a mixture of antagonists to ionic channels gated by glutamate (20 M 6-cyano-7-nitroquinoxaline-2,3-dione͞50 M 2-amino-5-phosphopentanoic acid), GABA (20 M bicuculline), and acetylcholine (1 M atropine͞5 M mecamylamine). In these experiments, voltage-gated sodium current was inhibited by extracellular tetrodotoxin (1 M), and voltage-gated current activated by hyperpolarization (I h current) was inhibited by intracellular QX-314 (5 mM) or tetraethylammonium (50 mM) (20,21). The dose-response relationship for activation by protons had an apparent Hill coefficient of 1.0 and an apparent EC 50 of pH 5.5 (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…46-50. Intracellular tetraethylammonium (50 mM) was used to block current activated by hyperpolarization (I h ) in some experiments (20). All chemicals were purchased from Sigma (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, isolated cerebellar nuclear neurons responded to SK channel blockade much like vestibular neurons in slices (du Lac, 1996). Finally, although trypsin can cleave I h (Budde et al, 1994), our control experiments with papaindissociated cells of the ventral cochlear nucleus suggest that I h can withstand our dissociation procedure.…”
Section: Other Currentsmentioning
confidence: 82%
“…First, in some neurons, I h is expressed preferentially in distal dendrites (Magee, 1998;Williams and Stuart, 2000), which are reduced in the dissociated cell preparation. Second, I h channels have been shown to be sensitive to enzymatic cleavage by trypsin (Budde et al, 1994), although the current has been recorded successfully in some papain-dissociated cells (Tabata and Ishida, 1996). Third, the voltage dependence of I h can be modulated by intracellular cAMP (Lüthi and McCormick, 1999), which may be submaximal under our recording conditions.…”
Section: H and Other Cation Currentsmentioning
confidence: 93%
“…The vast majority of protocols currently used to dissociate neural tissues into single cells rely on mechanical trituration after incubation in proteolytic enzymes (e.g., trypsin, papain, dispase, nagarse, pronase; see Drujan and Svaetichin, 1972;Lam, 1975;Kay and Wong, 1986;Huettner and Baughman 1986;Vaughan and Fisher, 1987;Montague and Friedlander, 1989;Mody et al, 1989). Unfortunately, several studies have shown that proteolytic enzymes can alter the amplitude, kinetics, localization, and pharmacological properties of voltage-and ligand-gated ion currents; these effects have been observed when enzymes are applied not only intracellularly but also extracellularly (e.g., Rojas and Armstrong, 1971;Lee et al, 1977;Hestrin and Korenbrot, 1987;Budde et al, 1994;Shen et al, 1995;Hermann et al, 1997;Armstrong and Roberts, 1998), and even as briefly as 1-3 min (Holt et al, 2001). These results have lead to attempts to isolate cells solely by mechanical means.…”
Section: Introductionmentioning
confidence: 99%